Note from the editor: In search of a pragmatist theory of inflation - Marcin Serafin (economic sociology. perspectives and conversations, 2023)
In 1976, standing before a cheering Wall Street audience at an event during the presidential campaign, US President Gerald Ford declared: 'After all, unemployment affects only 8 percent of the people while inflation affects 100 percent.' At the time, unemployment in the US fluctuated around 8 % while the annual inflation rate was around 5.5 %.
Keywords: 300